Measuring the impact of non-performing loans on credit-output frontier - Sylvia Fettry; Muliawati Muliawati; Amrie Firmansyah; Resi Ariyasa Qadri (Journal of Innovation in Business and Economics, 2025)
This research examines the efficiency of banking sectoral credit in generating economic output in East Java, with a focus on the impact of Non-Performing Loans (NPLs) on the credit-output efficiency frontier. Using quarterly sectoral data from 2012 to 2022 and implementing a stochastic frontier approach, this study decomposes NPLs into two categories: inefficient NPLs, arising from financing inefficiencies, and structural NPLs, originating from inherent credit risk and market risk. Subsequently, a dynamic fixed effects model is employed to test the impact of these decomposed NPLs on credit-output efficiency. The research results indicate that NPLs significantly influence credit efficiency. Inefficient NPLs tend to reduce credit-output efficiency in the short term, while structural NPLs diminish credit-output efficiency in both the short and long term. Based on these findings, enhancing sectoral credit-output efficiency necessitates improving banking risk management to reduce inefficient NPLs and maintaining macroeconomic stability to mitigate structural NPLs. Additionally, efforts to boost credit-output efficiency should focus on Gross Regional Domestic Product (GRDP) main sectors, such as manufacturing, trade, and logistics. Macroprudential incentives could be provided to banks that extend credit to priority sectors and exhibit low levels of inefficient NPLs. Concurrently, fiscal policy should aim to expand economic scale through infrastructure development, tax incentives, and accelerated technology adoption.